Effect of Gestational Age at Tenofovir-Emtricitabine-Efavirenz Initiation on Adverse Birth Outcomes in Botswana - Zash, Rebecca (J Pediatric Infect Dis Soc, 2018)
Among human immunodeficiency virus–positive women in Botswana on the recommended first-line antiretroviral therapy regimen, tenofovir-emtricitabine-efavirenz, initiated within the first or early second trimester, we found no increased risk of stillbirth, neonatal death, preterm/very preterm delivery, or the infant being born small or very small for gestational age. Treatment with tenofovir-emtricitabine-efavirenz <1 year before conception increased the risk of preterm delivery slightly over late-second-trimester treatment initiation (adjusted risk ratio, 1.33 [95% confidence interval, 1.04–1.70]).